The Effects of Rare Earth Pr and Heat Treatment on the Wear Properties of AZ91 Alloy - Ning Li; Hong Yan (Crystals, 2018)
This paper investigated the influences of Pr addition and heat treatment (T6) on the dry sliding wear behavior of AZ91 alloy. The wear rates and friction coefficients were measured by using a pin-on-disc tribometer under loads of 30, 60 and 90 N at dry sliding speeds of 100 rpm, over a sliding time of 15 min. The worn surfaces were examined using a scanning electron microscope and was analyzed with an energy dispersive spectrometer. The experimental results revealed that AZ91-1.0%Pr magnesium alloy exhibited lower wear rate and friction coefficient than the other investigated alloys. As the applied load increased, the wear rate and friction coefficient increased. Compared with the as-cast AZ91-1.0%Pr magnesium alloy, the hardness and wear resistance of the alloy after solution treatment were reduced, and through the subsequent aging, the hardness and wear resistance of the alloy were improved and the hardness was 101.1 HB (compared to as-cast AZ91 magnesium alloy, it increased by 45%). The AZ91-1.0%Pr with T6 magnesium alloy exhibited best wear resistance. Abrasion was dominant at load of 30 N, delamination was dominant at load of 60 N and plastic deformation was dominant at load of 90 N. Oxidation was observed at all loads.